THE ROLE OF LECTURING IN THE SCIENCE OF INFORMATION AND COMMUNICATION TECHNOLOGIES AND SYSTEMS IN THE ECONOMY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The role of lecture preparation during classes is generalized based on the authors' many years of experience using the example of the science of information and communication technologies and systems in economics.